Attitudes of accounting educators and financial managers in the UAE towards the general education requirements in learning accounting - Jamal Roudaki (Journal of Accounting, Business and Management (JABM), 2005)
Most universities and higher education institutions in developing countries seem to concentrate on areas of specialization in teaching accounting. Many do not seem to give attention to general education despite the fact that local and international accreditation bodies require general education to be part of the accounting degree. This paper aims at finding out how educators and financial managers differ in terms of their preference ratings of general education knowledge in accounting curricula. A survey was conducted and discriminant analysis was applied to the collected data. The results suggest that, the two groups differ in their preference in general education. financial managers seem to give more emphasis on general knowledge in the areas of art and science and business mathematics and statistics, while educators seem to pay more attention to general knowledge in marketing and economics